Siddha Medicine in Eastern Sri Lanka Today–Continuity and Change in the Treatment of Diabetes - Sathasivampillai, Saravanan V.; Rajamanoharan, Pholtan R. S.; Heinrich, Michael (Frontiers in Pharmacology, 2018)
Diabetes is affecting the social and economic developments in developing countries like Sri Lanka. Siddha Medicine (Tamil Medicine) is mostly practiced in the Eastern and Northern Provinces of Sri Lanka. Our recent review of Sri Lankan Siddha historical documents identified 171 plant species used to prepare anti-diabetic preparations. On the other hand, there is no study of plants currently used to treat diabetes in Sri Lankan Siddha Medicine. Hence, the aim of this study is to identify and document the plant species currently used in anti-diabetic preparations in Eastern Province, also enabling a comparative analysis with historical uses. Further, assessing the level of scientific evidence (in vitro, in vivo, and clinical studies) available for recorded species. A systematically prepared questionnaire was used to conduct an ethnobotanical survey with 27 Siddha healers residing in Eastern Province to identify the currently used anti-diabetic plants. Furthermore, Web of Science electronic database was used to assess the level of scientific evidence available excluding widespread and very well studied species. On average 325 diabetic patients were seen by 27 healers per week. Interestingly, inorganic substances and animal parts used as ingredients in historical anti-diabetic preparations are currently not used in Eastern Province. A total of 88 plant species from 46 families were reported in this study. Syzygium cumini (L.) Skeels was the most frequently recorded species and the largest number of taxa are from Fabaceae. Remarkably, one third of reported species were not stated in Sri Lankan Siddha historical documents. The highest number of plant species (59%) have been studied up to an in vivo level followed by no scientific evidence for anti-diabetic activity found (27%), clinical evidence (10%), and in vitro (2%). This is the first ethnobotanical study of plants used to treat diabetes by Siddha healers in the Eastern Province in Sri Lanka. Moreover, awareness should be created to the diabetics about the side effects of herb-drug interactions and complications caused by taking both herbal preparations and biomedical drugs.